KONFLIK ANTAR INDIVIDU DAN PENGARUHNYA PADA EFEKTIFITAS TIM - Hapsari, Ira Maya (PERMANA, 2010)
Team have more value than a group. Team have higher cohesiveness and thighter commitment even of the group has. Everybody guessing that team have a heavier task than a group, therefore, team need a highly cooperation, which canât be happen if there was any conflict interpersonal inside the team. Even so, conflict not must be eliminate, because, surprisingly, conflict able to improve the team effectiveness, with the right manage for it, of course. Conflict can be direct to the brainstorming area, that can brought all member of the team understanding every oneâs the way of thinking. Brainstorming allow everybodies to see and learn for the everybody thougt, accept it with clear thougt and open minded also act professional, free, and independent.Making those thing come true, every body on the team must be cooperative, wisely undesrstanding, open minded, and not pretending. If these thing have done, donât bother, conflict will end soon, and team effectiveness also team productivity will easy to achieve. Keywords : interpersonal, team effectiveness, conflict